Parents’ perceptions of the competency-based approach in the Algerian curriculum: A study of fifth-grade Pupils’ Families - Naima, Bouaoud (The International tax journal, 2025)
This study aimed to analyze the perceptions of parents of fifth-grade pupils regarding the competency-based approach in the Algerian curriculum and to explore the social, cultural, and educational factors influencing these perceptions, as well as their impact on family support for the learning process. The research employed a descriptive-analytical method, using questionnaires and observation to collect data from a clustered sample of 167 parents. The data were statistically processed using SPSS, complemented by a sociological analysis of social representations and the family’s role in learning. The results revealed that the majority of parents (90%) have experience in supervising lesson reviews and homework completion, and 64% expressed support for the new educational reforms. Understanding of the curriculum was found to be related to parents’ educational level, with higher comprehension rates among those with higher education. Parents reported difficulties, primarily lesson density, the volume of homework, and comprehension challenges, and 65% utilized social media to express their concerns. The study indicates that the family serves as an indirect educational agent in supporting children’s learning, and that coordination with schools and enhanced communication through social workers contributes to improving understanding of the competency-based approach and activating the family’s role.